Night of the living dummy II - Stine, R. L. (Scholastic New York, 1995)
Amy's ventriloquist dummy, Dennis, keeps losing his head. So Amy begs her family for a new dummy. That's when her dad finds Slappy in a local pawnshop. Slappy's kind of ugly, but Amy's having fun practicing her new routine. Then horrible things start happening. Horrible, nasty things. Just like what happened the first time. Because there's something odd about Slappy. Something not quite right. Something evil